An Effect of Output Capacitor ESL on Hysteretic PLL Controlled Multiphase Buck Converter - M. Jelinek; J. Jakovenko (Radioengineering, 2017)
This paper provides analysis of output capacitor effects to phase stability of a hysteretic mode controlled buck converter. The hysteretic control method is a simple and fast control technique for switched-mode converters, but the hysteresis control is not oscillator referenced. It results in difficulty to achieve stable switching phase and frequency. In recent papers, the authors propose a use of phase locked loops (PLL) to permit interleaved multiphase operation where each voltage regulator (VR) module is coupled together via output node and leads to a strong loop interaction. In this work analysis of this interaction is studied by Matlab Simulink simulations and a new solution how to partially suppress this effect is given. The proposed method confirms the theoretical analysis.